Study of socio-demographic factors affecting prevalence of hypertension among bank employees of Surat City - Mohmmedirfan H Momin; Vikas K Desai; Abhay B Kavishwar (Wolters Kluwer Medknow Publications, 2012)
Cardiovascular diseases including hypertension are increasing in developing countries especially among high-risk group people like bank employees. A cross-sectional study of 1493 bank employees of Surat city was conducted during August, 2004 to September, 2005 to study the prevalence of hypertension among bank employees and the effects of socio-demographic factors on prevalence of hypertension. Data were analyzed using epi 6 software. The χ[2] -test was applied as a nonparametric test of statistical significance. Prevalence of hypertension was 30.4% and prehypertension was 34.5%. Out of 455 found as hypertensive, 258 (56.70%) were not having any symptoms at the time of examination. Prevalence was high among persons with age 50 years and above (48.5%); among male (32.5%) as compared to female (23.1%); among employees having small family size; among separated/divorcee person (40.0%). Prevalence of hypertension increased with seniority of the official position of bank employee with highest prevalence among managers (45.9%). Prevalence of hypertension was noted highest among the higher socioeconomic group; SEC I (35.0%) followed by class II (20.4%). Effects of different risk factors of hypertension were observed here. This study may help in identifying the common profile of hypertensive or persons at risk, which may further help in identifying the risk group and planning the group specific IEC interventions.